AGRESIVITAS KEBIJAKAN LUAR NEGERI TIONGKOK DALAM SENGKETA WILAYAH DENGAN FILIPINA DI PULAU THITU - Karmilawaty, Ratu Salmazahra; Janvy, Canytea (Department of International Relations Universitas Satya Negara Indonesia, 2024)
This research aims to describe China’s aggressive foreign policy in its territorial disputes with the Philippines in Thitu Island in Spratly Islands, South China Sea. The two countries both claim to own Thitu for its rich natural resources. The territorial claims of China and the Philippines over Thitu have escalated the territorial conflict in South China Sea and threatened the regional stability in Southeast Asia. This research seeks to discuss the implementation of China’s aggressive foreign policy that the Philippines consider as a threat to its territorial claim over Thitu Island. As such, this research employs a qualitative method, with offensive realism theory in place. This research argues that the anarchic world system triggered China’s aggressive foreign policy in a way that the country deploys its vessels to the island to deter the Philippines and claim Thitu. For China, obtaining Thitu’s rich natural resources are national interests that the country intends to reach in South China Sea. China intends to control Thitu in a bid to strengthen its economic and military power. China’s military actions around Thitu represent its foreign policy to claim the entire South China Sea.